Assessing the Impact of Customer Relationship Management (CRM) on the Overall Productivity of Government-Owned Organizations - Goldar, Sufal Chandra (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This analysis investigates the effects of Customer Relationship Management (CRM) on the total productivity of state-operated entities in Bangladesh. As public sector organizations strive to enhance service efficiency, citizen engagement, and accountability, CRM has emerged as a viable digital solution. A systematic questionnaire was used to gather data from 400 personnel across three governmental organizations: Dhaka Electric Supply Company Limited (DESCO), Dhaka Water Supply and Sewerage Authority (WASA), and Bangladesh Telecommunications Company Limited (BTCL). Statistical evaluations, including correlation analysis and multiple regression techniques, were employed to assess five hypotheses regarding CRM implementation, productivity, employee engagement, citizen satisfaction, and the impact of governance and implementation challenges. The results indicate that adopting CRM substantially enhances productivity and citizen satisfaction while improving employee engagement. Nevertheless, the existence of technological and organizational impediments was determined to have an adverse impact on the efficacy of CRM. Furthermore, support from governance—manifested through leadership, policy formulation, and oversight—plays a crucial role in sustaining CRM outcomes. This study concludes that CRM, when executed with strategic foresight and institutional backing, possesses the potential to transform public sector performance within Bangladesh. This investigation provides empirical evidence and insights relevant to policymaking efforts aimed at advancing digital governance in developing nations.